Impregnation of Se2S6 into a Nitrogen- and Sulfur-Co-Doped Functional Metal Carbides and Nitrides for High-Performance Li-S Batteries - Lu Chen; Zhongyuan Zheng; Shuo Meng; Wenwei Wu; Weicheng Zhou; Shanshan Yang; Kexuan Liao; Yuanhui Zuo; Ting He (Molecules)
In this study, nitrogen- and sulfur-co-doped MXene (NS-MXene) was developed as a high-performance cathode material for lithium–sulfur (Li-S) batteries. Heterocyclic Se2S6 molecules were successfully confined within the NS-MXene structure using a simple melt impregnation method. The resulting NS-MXene exhibited a unique wrinkled morphology with a stable structure which facilitated rapid ion transport and provided a physical barrier to mitigate the shuttle effect of polysulfide. The introduction of nitrogen and sulfur heteroatoms into the MXene structure not only shifted the Ti d-band center towards the Fermi level but also significantly polarizes the MXene, enhancing the conversion kinetics and ion diffusion capability while preventing the accumulation of Li2S6. Additionally, the incorporation of Se and S in Se2S6 improved the conductivity compared to S alone, resulting in reduced polarization and enhanced electrical properties. Consequently, NS-MXene/Se2S6 exhibited excellent cycling stability, high reversible capacity, and reliable performance at high current densities and under extreme conditions, such as high sulfur loading and low electrolyte-to-sulfur ratios. This work presents a simple and effective strategy for designing heteroatom-doped MXene materials, offering promising potential for the development of high-performance, long-lasting Li-S batteries for practical applications.